Black ice : [large type] a thriller - Thor, Brad (Thor, Brad. Scot Harvath, 2021)
"With a cottage on the fjord, a boat, and his beautiful girlfriend, Sølvi, Scot Harvath's got everything he could possibly want. But leaving his favorite Oslo café, Harvath watches as a ghost climbs out of a taxi--a man he killed years ago, halfway around the world. How is he still alive? And what is he doing in Norway? In a race against time that will take him high above the Arctic Circle, Harvath will be tested in ways he has never imagined and pushed to a limit few human beings could ever endure. If he succeeds, he'll walk away with everything. If he fails, the United States and its allies will be at the mercy of one of the world's most dangerous actors"--Page 4 of cover.